Research From the Global South: The important role of context in international research activities - Bryant, Katie (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2014)
Researchers from various disciplines have become interested in the supposedly extreme differences in rates of research between academics situated in the Global North and South, specifically those on the African continent. Yet, having worked as a researcher and a writing coach in the context of one university in the southern African region for the past three years, I cannot identify with many of the explanations given for these differences in rates. So, by reflecting on two instances emerging from my own experiences as a researcher in this particular context, this Note from the Field discusses the important and critical role context needs to have in making sense of this phenomenon.